Reforming European Universities: The Welfare State as a Missing Context - Marek Kwiek (Voprosy obrazovaniya / Educational Studies Moscow, 2015)
The argues that welfare state reforms and higher education reforms are closely linked to increasing intergenerational conflicts over public resources in aging societies, and reforms pressures are linked to the shrinking tax base, the power of neoliberal ideology, and changing social attitudes across Europe. The indirect impact of aging societies on all public sector services will lead to growing pressures on all public expenditures and to increased competition for public funding. A new context of university reforms in Europe is therefore defined in this paper as welfare state reforms. The paper discusses global agenda-setting and global diffusion of ideas; the impact of aging societies on intergenerational conflicts over public priorities (and public resources); globalization and pressures on welfare states; “university attitudes”, parallel to “welfare attitudes”; post-industrial societies; the role of supportive discourses in the survival of public institutions; and the role financial and ideological pressures, as well as of changing social beliefs, in reforming European welfare states and higher education.